VOCATIONAL HIGH SCHOOL STUDENTS' PERCEPTIONS OF USING AI FOR LEARNING ENGLISH: BENEFITS AND CHALLENGES - Yuniarti Yuniarti; Sri Rahayu Pebriani (Journal of English Educational Study (JEES), 2026)
This study investigates vocational high school students’ perceptions of using artificial intelligence (AI) in English language learning, focusing on both the benefits and challenges. The research was conducted with 11th-grade students at SMK Model Patriot IV Ciawigebang, Kuningan, West Java, Indonesia, employing a mixed-methods design. Quantitative data were collected through structured questionnaires, while qualitative insights were obtained from open-ended responses and semi-structured interviews. The findings indicate that students perceive AI as a supportive tool that enhances comprehension, enriches vocabulary, improves efficiency, and provides instant feedback, thereby fostering greater autonomy in learning. However, students also expressed concerns about information overload, inaccurate or irrelevant feedback, overreliance on AI for assignments, superficial learning, and ethical issues such as plagiarism. These dual perceptions highlight AI’s ambivalent role as both a facilitator and a potential risk in language education. For vocational students, whose learning is closely tied to employability, this paradox underscores the necessity of embedding AI within pedagogically sound frameworks that balance accessibility and innovation with critical thinking and ethical awareness. The study contributes to the growing body of literature on AI in education by offering context-specific insights from Indonesia and emphasizing the importance of careful integration of AI in vocational English instruction.